Huet e Régis : interpretações da dúvida cartesiana em disputa - Bruna Ribeiro Martins (2020)
The aim of this work is to investigate the reception of cartesian doubt by two authors of the late seventeenth century: Pierre-Daniel Huet (1630-1721) and Pierre-Sylvain Régis (1632-1707). The works to be considered are Descartes’s Meditations of First Philosophy, Huet’s Censura Philosophiae Cartesianae and Régis’s Réponse au livre qui a pour titre “P. Danielis Huetii,...Censura philosophiae cartesianae”. We will analyse the particularities of each reception, considering the doubt presented by Descartes in the First Meditation and its function in his philosophy. The hypothesis to be developed is that the reception of Huet, who denies the positive philosophy of Descartes due to the view that there is no possible certainty after Descarte’s doubt, is more consistent than the interpretation offered by Régis, who mitigate the radical value of cartesian doubt due to his compromises with an empricist view of cartesianism.